FORMULASI OBAT-OBAT ḤALĀLAN ṬAYYIBAN - Muhamad Ikhwan Lukmanudin (IAIN Ambon, 2017)
This study proved that the drug may be formulated according to the principles of Islamic (Halal) and pharmacists (Tayyib). Class of drugs mukolitik, antiamuba, decongestants, antihistamines, antacids, anti-tuberculosis, antiasma, antitussive, antipyretic, analgesic, anti-inflammatory non-steroidal, antihemoroid, laksativum and antibiotic formulated using solvents, preservatives, dyes, flavors, emulsifiers, suspending agents, antioxidants and stabilizers (halal) Islamic perspective (according to the provisions, standards and CPOH or how to manufacture drugs kosher LPPOM MUI), and tested the stability and effectiveness include the analysis of organoleptic (al-Taghayyur al-Ḥissiyu), sedimentation, dispersion, pH (Al-Taghayyur al-Taqdīriy), viscosity, retention factor, percent grade and examination preparation with good value (Tayyib) pharmacist's perspective (as applicable, and GMP standards or ways of making good remedy of POM RI). This study supports the Act 33 of 2014 About Halal Product Guarantee and the Indonesian Ulema Council decision in 2010 that, medicines must be guaranteed halal. This study is different from the Ministry of Health and Ministry of Industry that, the drug does not need to be formulated (kosher) because it is difficult and only disrupt investment. Opposing theories of the ulama is Dzulkifly Mat Hashim (2010), and Sahal Mahfudh (d.2014 M) as well as among pharmacists Kyoko Kogawa Seto (2012) and Amanda K. Gilmore (2013) concurred that the illicit material is allowed in moderation in the treatment for ' illat emergency and moderation. This research in the Research and Development includes descriptive stage (preformulsi), experimental (formulation) and evaluative (stability test and evektifitas). The research concludes while, that the illicit drugs that have been made lawful for 'emergency illat lost with the discovery of a drug that is Halal and Tayyib (ما جاز لعذر بطل بزواله). Keywords: formulation, drug, kosher, tayyib, Islam and pharmacists